2022
DOI: 10.1007/s00018-021-04095-z
|View full text |Cite
|
Sign up to set email alerts
|

Plasmolipin regulates basolateral-to-apical transcytosis of ICAM-1 and leukocyte adhesion in polarized hepatic epithelial cells

Abstract: Apical localization of Intercellular Adhesion Receptor (ICAM)-1 regulates the adhesion and guidance of leukocytes across polarized epithelial barriers. Here, we investigate the molecular mechanisms that determine ICAM-1 localization into apical membrane domains of polarized hepatic epithelial cells, and their effect on lymphocyte-hepatic epithelial cell interaction. We had previously shown that segregation of ICAM-1 into apical membrane domains, which form bile canaliculi and bile ducts in hepatic epithelial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 50 publications
3
12
0
Order By: Relevance
“…Differentiated organoids formed spheroids (Figure A,B). In addition to secreting albumin and processing CFDA (not shown), , electron microscopy analyses confirmed that organoid cells formed lateral cavities between them, which have been shown to functionally resemble bile canaliculi upon differentiation …”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Differentiated organoids formed spheroids (Figure A,B). In addition to secreting albumin and processing CFDA (not shown), , electron microscopy analyses confirmed that organoid cells formed lateral cavities between them, which have been shown to functionally resemble bile canaliculi upon differentiation …”
Section: Resultsmentioning
confidence: 81%
“…(B) Differentiated organoids from WT and MDR2KO mice were fixed and processed for transmission electron microscopy. Cells are organized in sheets facing big central lumens (left and central images) and form smaller cavities between their lateral membranes containing cell–cell junctions and microvilli (right images), which have been shown to have functional features resembling bile canaliculi and contain canalicular markers …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We had previously shown that ICAM-1 is expressed in sinusoids but also concentrates in the bile canaliculi and bile ducts of polarized hepatic epithelial cells of the human liver parenchyma (Figure 1A) (Reglero-Real et al , 2014). HepG2 cells are spontaneously polarized human hepatic epithelial cells that form actin-rich, bile canalicular-like structures (BCs) and are thus a prototypical in vitro model for studying hepatic apicobasal polarity (Reglero-Real et al , 2014; Lazaro-Dieguez & Musch, 2017; Madrid et al , 2010; van Ijzendoorn et al , 1997; Cacho-Navas et al , 2022). To investigate the role of ICAM-1 on hepatic epithelial cell polarity, we first generated HepG2 cells in which the ICAM-1 gene was edited using CRISPR/CAS9 (ICAM-1_KO cells) (Figure 1B and C).…”
Section: Resultsmentioning
confidence: 99%
“…The apical membrane domains of hepatocytes and cholangiocytes form bile canaliculi and bile ducts, respectively, which drain bile acids and other hepatic molecules into the gastrointestinal tract. The composition of the apical plasma membrane domains in these small channels differs from that of basolateral membranes and from plasma membranes in non-polarized cells, and is determined by an actin cytoskeletal network, which concentrates in these apical domains, and by mechanisms of polarized intracellular sorting of proteins and lipids towards these membrane regions (Meyer et al , 2020; Tsukada et al , 1995; Fu et al , 2010; Cacho-Navas et al , 2022; Musch, 2014). The filamentous actin cytoskeleton in the bile canaliculus forms small membrane protrusions, called microvilli, which contain actin but not myosin.…”
Section: Introductionmentioning
confidence: 99%